Organ Shortage, Will Peoples Knowledge be a Path to the Solution? - Félix Cantarovich (Highlights on Medicine and Medical Research Vol. 12, 2021)
Organ shortage transforming death into life, which is what organ transplants symbolize, needs the end of somebody life, a scientific miracle of our times, but as well a social problem. Prejudices or ignorance inhibits to offering life to another human being. The consequence of this conflicting situation is that patients waiting for transplantation, “unfairly” die every day. States and Social Security should be involved in this problem. Programming efficient education will be important for change social conduct towards organ donation. As well, several studies emphasize the persistence of an insufficient university medical teams training in transplantation. Organ shortage and waiting lists patients’ mortality is a failure of social communication on organ donation and transplantation. Proposals to review social and university education in current organ shortage crisis, might be an ethical duty for states health and education officials. Solidarity is a positive peoples feeling, nevertheless faced with death of a loved one; it does not seem to be an enough reason to justify authorization to donate. For many people, organ donation represents a perverse and unjustified action of mutilation. Considering the negative reactions that often can occur in the moment in which the alternative of deciding the donation of organs of a loved one is presented; we have proposed the inclusion in the social education plans the following concepts: Organ shortage is a health emergency. Throughout our lives, we might need organ or tissue transplantation. Our body after death is a unique source of health to be shared Organ donation meant to” share life” more than “to gift life”. Organ donation should be a social agreement. People should know the social risks involved in establishing economic incentives for donation. This analysis is made to provide a basic knowledge of a vital medical crisis, and to suggest to decision makers of educational programs useful suggestions for this serious problem. In addition, and very particularly this work is directed to the Society, the main protagonist of this problem, requiring to receiving a correct and detailed information on the dilemma of the lack of organs, in quest that the donation decision will be an act of full awareness. A French philosopher, Jean Rostand has said "To dream you have to know".